Infusing the concept of aqil baligh for early childhood - Wahidah Wahidah (Institut Agama Islam Negeri Langsa, 2021)
The article discusses the concept of teaching and learning aqil baligh in early childhood and given the importance of one readiness in carrying out one duty as a mukallaf when it has reached aqil baligh. Teaching and learning aqil baligh for early age children is not a provision of obligations but rather a preparation, training, and habituation to welcome the period of imposition of obligations (taklif) when he is baligh later. This is qualitative research based on a literature review. Data collection of this study was from books, journals of research results related to early childhood education. Early childhood education (between 0- 7 years) emphasizes the attainment of one's awareness of carrying out orders and abandoning the prohibitions of God. Learning material includes aqidah, worship (ibadah), and morals (akhlak) with several models. Early Childhood Education teachers must develop and model it for the children.